An Investigation on Online Metacognitive Reading Strategies Used by Malaysian Engineering Undergraduates - Kangxing, Dong; Swan, Chiam Kee; Hafizoah, Kassim (Penerbit UMP, 2022)
With the prevalent use of computers and Internet, online reading has become an indispensable part of students’ academic life. Applying reading strategies to improve comprehension in online reading context plays a significant role in students’ learning success. Metacognitive reading strategies serve as the effective tool to enhance reading comprehension. The purpose of this study is to explore the overall profile of online metacognitive reading strategies used by Malaysian engineering undergraduates while reading English academic materials. The data were collected by using the questionnaire adapted by the researcher from previous questionnaire. The findings revealed that the participants’ use of online metacognitive reading strategies was relatively moderate. Problem-solving strategy was the most used category of metacognitive strategies, while support reading strategy was the least used. Teachers are suggested to provide explicit instruction in terms of metacognitive reading strategies, as well as how to apply them in online contexts.